Recommendations on the follow‐up of patients with Gaucher disease in Spain: Results from a Delphi survey. Issue 1 (8th November 2022) - Giraldo, Pilar; Andrade‐Campos, Marcio; Morales, Montserrat; ,
Abstract: Management of Gaucher disease (GD) is challenging due to its wide genotypic and phenotypic variability and changing clinical manifestations due to effective treatment. Sixteen face‐to‐face meetings with experts were held in order to discuss daily clinical practice and identify controversies regarding the management of GD. With this information, a questionnaire with 93 recommendations for different clinical scenarios was designed, and a Delphi survey among 86 physicians with experience in GD was conducted. Consensus was reached on 73 out of the 93 items. Recommendations on follow‐up of adult and pediatric patients were in line with current guidelines, and underscored the importance of a patient‐tailored approach. For the follow‐up of stable patients receiving long‐term treatment, consensus was reached on the importance of multidisciplinary care that involves pediatricians, internal medicine, and primary care, specialized radiologists, orthopedic surgeons, and hematologists when required. Degree of pain, use of painkillers and antidepressants, and quality of life should be evaluated at every follow‐up visit or at least once per year. In general, a closer follow‐up was recommended for untreated patients or patients who underwent a treatment change (every 3 months during the first year) and during pregnancy. For pregnant patients, hemostasis and risk of hemorrhage should be assessed, but no consensus was reached for initiation of treatment in asymptomatic pregnant patients. Lastly, recommendations on how to adapt GD management during a COVID‐19 pandemic were collected. This expert consensus may help decision‐making during the management of GD in specific clinical scenarios.